The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/hpb.12161
|View full text |Cite
|
Sign up to set email alerts
|

Using a standardized method for laparoscopic cholecystectomy to create a concept operation-specific checklist

Abstract: A standardized approach to LC would allow for the creation of an LC-specific checklist that has the potential to lower the prevalence of BDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 35 publications
(52 reference statements)
1
75
0
1
Order By: Relevance
“…Other strategies designed to reduce bile duct injuries, including the use of the anatomical landmark Rouvière's sulcus or a cholecystectomy checklist, have not been rigorously tested. 26,27 This study has some limitations. The primary aim of the CholeS study was to assess the variation in practice of cholecystectomy in the UK and was not designed to develop a risk score to predict conversion.…”
Section: Discussionmentioning
confidence: 95%
“…Other strategies designed to reduce bile duct injuries, including the use of the anatomical landmark Rouvière's sulcus or a cholecystectomy checklist, have not been rigorously tested. 26,27 This study has some limitations. The primary aim of the CholeS study was to assess the variation in practice of cholecystectomy in the UK and was not designed to develop a risk score to predict conversion.…”
Section: Discussionmentioning
confidence: 95%
“…The key to safe dissection is the dissection technique used. The two cases that lead to this study, as well as one recently reported, use the principles of dissection described by Connor et al , which has not been previously reported for LSGB. The initial dissection commences on the gallbladder, dissecting the gallbladder off the cystic plate .…”
Section: Discussionmentioning
confidence: 99%
“…The article stated dissection of hepatobiliary triangle should be lateral to LN to minimize the risk of BDI [9]. Hepatobiliary (previously called Calot's) triangle in modern practice consists of the cystic duct as the inferior border, common hepatic duct as the medial border and inferior border of the liver as the superior border.…”
Section: Discussionmentioning
confidence: 99%